Water, Air, & Soil Pollution - Water, Air, & Soil Pollution (Springer Nature, 2026)
Water, Air, & Soil Pollution is an interdisciplinary journal publishing research on all aspects of pollution and solutions to pollution in the biosphere. Covers chemical, physical, and biological processes affecting flora, fauna, water, air, and soil. Accepts papers on methods used in the study of environmental pollutants and related disciplines. Welcome submissions in environmental and molecular toxicology applied to pollution research, biosensors, climate change, ecological implications of pollution and models. Publishes internationally relevant novel knowledge for more than 5 decades. Currently invites review papers on subject areas under the scope of this journal. Please contact the Editors-in-Chief with review proposal.
FI 0.57
Q2
Keywords: Earth; Space & Environmental Sciences; Environmental Science; Ciencia ambiental; Edafología; Acuerdos transformativos; Transformative agreements; Procesos químicos; Procesos físicos y biológicos; Flora; Fauna; Agua; Aire; Suelo